Território quilombola do Curiaú e área de proteção ambiental do Rio Curiaú: interpretações dos conflitos socioambientais pela economia ecológica - QUEIROZ, Silvaneide (Universidade Federal do Pará, 2011)
This research is based on a study of the existing social, economic, environmental and political relations within the Quilombola territory, Curiaú, located within the municipality of Macapá, state of Amapá. The objectives of this study were to analysis the regulations governing the system of communal (resource) use as adopted by Quilombola families, considering the existing conflicts within these territories in relation to the pressure on natural resources as a result of the interferences of institutions such as the state and the market. This study is primarily based on field study when fifty-five (55) questionnaires were administered during the period that extended from June to August, 2006. The presence of new resource use regulations governing lands occupied by the Quilombolas has contributed towards the overexploitation of resources available in some ecosystems. In relation to market forces and the enactment of environmental policies and government programmes, it was possible to observe changes in the regulations governing the system of communal resource use as adopted by Quilombola families. Finally, the study confirmed the need for strengthening the debate on communal use of natural resources and its importance for the maintenance and survival of Quilombola families in Curiaú.